2019
DOI: 10.1094/pdis-10-18-1867-re
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Fungicides and Their Application Timing for the Management of Sorghum Foliar Anthracnose in the Mid-Atlantic United States

Abstract: Sorghum anthracnose (Colletotrichum sublineola) reduces grain yield up to 50% but suggested management tactics have not yet been developed for the mid-Atlantic United States, where warm, wet conditions favor disease. Under factorial arrangement, five fungicides plus a nontreated control and four application timings were compared for foliar anthracnose control, yield, and profitability of fungicide use in grain sorghum over eight site-years in Virginia and North Carolina. Anthracnose severity was rated at the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…13 In a study on effectiveness of fungicides and their application timing for the management of sorghum foliar anthracnose in the mid-Atlantic United States, Acharya concluded that Pyraclostrobin and Pyraclostrobin plus Fluxapyroxad controlled anthracnose disease of sorghum. 26 These studies reveal that a combination of Pyraclostrobin and Fluxapyroxad is effective in the control of Anthracnose and other fungal pathogens.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…13 In a study on effectiveness of fungicides and their application timing for the management of sorghum foliar anthracnose in the mid-Atlantic United States, Acharya concluded that Pyraclostrobin and Pyraclostrobin plus Fluxapyroxad controlled anthracnose disease of sorghum. 26 These studies reveal that a combination of Pyraclostrobin and Fluxapyroxad is effective in the control of Anthracnose and other fungal pathogens.…”
Section: Discussionmentioning
confidence: 98%
“…The results of this study are in agreement with. 13,25,26 In a study on the in vitro evaluation of commercial fungicides against some of the major soil borne pathogens of soybean, Navi concluded that a combination of Pyraclostrobin and Fluxapyroxad controlled several fungal pathogens that included; Fusarium virguliforme, Macrophomina phaseolina, Rhizoctonia solani, and Sclerotinia sclerotiorum. 25 In a study on the evaluation of pre-mix fungicide, fluxapyroxad and pyraclostrobin 500 sc against powdery mildew disease of mango (Oidium mangiferae), Ravikumar confirmed that the fungicide significantly reduced the disease severity and increased the mango productivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), head blight, ergot (head smut; Claviceps africana), bacterial leaf stripe (Burkholderia andropogonis), and rust (Puccinia purpurea). Anthracnose can result in yield losses of over 50% (Acharya et al 2019) and head mold can potentially produce detrimental or lethal mycotoxins. Most yield loss occurs from stalk rot pathogens such as charcoal rot (the same disease previously discussed with corn).…”
Section: Diseasesmentioning
confidence: 99%
“…Agronomic practices alone are not effective to reduce infections and yield losses due to anthracnose. Although fungicide application is an effective method to control the disease and reduce yield losses (Acharya et al, 2019), it is not economically and practically feasible for small-scale farmers and is not environmentally friendly. Growing sorghum cultivars resistant to anthracnose is considered the most efficient and is a core in integrated strategy for anthracnose management.…”
Section: Introductionmentioning
confidence: 99%